DIGITAL TRANSFORMATION OF BUSINESS MODELS IN PRIVATE MEDICINE: CHALLENGES AND OPPORTUNITIES - VOZNYI, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article examines the impact of digital transformation on the business models of private medicine in Ukraine, evaluates its economic efficiency, and analyzes ways to overcome key challenges, including financial, regulatory, and technological aspects. Despite the availability of research highlighting general trends in the digitalization of healthcare, there is a lack of studies dedicated specifically to the business models of private medical institutions in the Ukrainian context. Comprehensive assessments of the economic feasibility of implementing digital technologies in the private sector, as well as mechanisms for integrating digital solutions within the existing legal framework, are also lacking. The issue of financing digital transformation remains particularly relevant. Models for attracting investment and opportunities for public-private partnerships to implement innovative technologies are insufficiently explored. The absence of a nationwide program to support digital initiatives in private healthcare creates barriers to large-scale implementation. Insufficient integration of medical IT solutions with modern cybersecurity standards poses risks of confidential data leaks and reduces patient trust in digital platforms. Despite the active adoption of digital tools, a low level of digital literacy persists among some medical staff. There are no comprehensive training programs for working with electronic medical records, artificial intelligence, and clinic management platforms, which hinders adaptation and reduces the effectiveness of new technologies. Over the last decade, digital technologies have become a key driver of change in healthcare. In the private sector, digitalization helps improve service quality, reduce operating costs, and make medical care more accessible to the population. In Ukraine, this process is only gaining momentum, combining significant opportunities with serious challenges. This article focuses on analyzing the c